The Relationship Between Career Success Expectations and Emotional Intelligence with Quarter Life Crisis in Generation Z - Caesarani, Ericha Setya; Mahardayani, Iranita Hervi (Journal Research of Social Science, Economics, and Management, 2026)
Quarter-life crisis has emerged as a significant psychological phenomenon affecting Generation Z, characterized by identity confusion, career uncertainty, and emotional instability during the transition to adulthood. This study aims to determine the relationship between career success expectations and emotional intelligence with quarter life crisis in generation z. Respondents in this study were generation z aged 18-19 years and unmarried totaling 66 respondents. The sampling technique used was purposive sampling. The research instrument used a quarter life crisis scale, career success expectations and emotional intelligence. The results of the correlation coefficient of the three variables are 0.504 with a p-value of 0.001 (p<0.01) and an effective contribution of 25.4%, meaning there is a very significant relationship between career success expectations and emotional intelligence with quarter life crisis. The results of the first minor hypothesis test showed that there is a very significant negative relationship between career success expectations and quarter life crisis with a correlation coefficient of -0.346 and a p-value of 0.002 (p<0.01). The results of the second minor hypothesis test also showed a very significant negative relationship between emotional intelligence and quarter life crisis with a correlation of -0.447 and a p-value of 0.001 (p<0.01). Based on the research results, it can be concluded that the three variables have a significant negative relationship between both career success expectations and quarter life crisis and emotional intelligence and quarter life crisis.